Size dependence of vortex-type spin torque oscillation in a Co2Fe0.4Mn0.6Si Heusler alloy disk. (31st January 2018) - Seki, T; Kubota, T; Yamamoto, T; Takanashi, K
Abstract: This paper reports the systematic investigation of vortex-type spin torque oscillation in circular disks of highly spin-polarized Co2 Fe0.4 Mn0.6 Si (CFMS) Heusler alloys. We fabricated the current-perpendicular-to-plane giant magnetoresistance (CPP-GMR) devices with various disk diameters ( D ) using the layer stack of CFMS/Ag3 Mg/CFMS. The gyrotropic motion of the vortex core was successfully excited for the CFMS circular disks with 0.2 µ m  ⩽   D   ⩽  0.3 µ m. The CPP-GMR device with D   =  0.2 µ m exhibited the Q factor of more than 5000 and the large output power of 0.4 nW owing to the high coherency of vortex dynamics and the high spin-polarization of CFMS. However, the Q factor was remarkably decreased as D was reduced from 0.2 µ m to 0.14 µ m. The comparison with the calculated resonance frequencies suggested that this degradation of the Q factor was due to the transition of the oscillation mode from the vortex mode to other modes such as the low-coherent out-of-plane precession mode. The present experimental results also suggest that there exists an adequate disk size for the enhanced Q factor of the vortex-type spin torque oscillation.